Are Powerful Majorities Inefficient for Parties and Efficient for Taxpayers?: An Analysis of Budget Maximization in the United States. (January 2014) - Mitchell, David T.; Hughes, Danny R.; Campbell, Noel D.
Recent studies examining the relationship between legislative majorities and state budgets have presented mixed results. We provide new insight on this relationship by employing stochastic frontier analysis to model the maximum potential budgets that could be feasibly produced, given a set of economic, political, and voter inputs. This allows us to examine directly how the size of ruling party majorities influences their ability to efficiently produce the maximum feasible budget. At the same time, we are able to analyze the inefficiency in budget maximization. We find that as parties consolidate power with large majorities—regardless of party identity—they are less able to maximize budgets leading to state budgets below the maximum possible size of government as estimated by our model. Our results suggest that parties that do not maximize spending are inefficient at spending but efficient at providing the services that voters want at a low price. Hence, those parties build larger coalitions.